Analisis Dampak Kebijakan Pengendalian Harga Pangan Terhadap Daya Beli Masyarakat (Studi Kasus Pasar Tradisional Di Kabupaten Labuhan Batu Selatan) - Harahap, Anhar Nurdiansyah; Sugianto, Sugianto; Atika, Atika (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to examine the impact of food price regulation policies on people's purchasing power in South Labuhan Batu Regency. This research method uses a descriptive qualitative approach, which involves collecting data through interviews conducted with 5 traders and 15 buyers in traditional markets. Data analysis involves the process of data reduction, data writing, and verification to arrive at research conclusions. The research results show that policies aimed at controlling food prices contribute positively to price stability and increase people's purchasing power. Based on research results, traders recognize the benefits of price stability even though their profit margins are decreasing. The same thing is felt by fruit and fish sellers, who experience price stability but have to face high operational costs and decreasing profit margins. For consumers, this policy helps reduce the burden on household expenses, even though product quality and availability of goods are sometimes inconsistent. From an Islamic economic perspective, this policy is in line with the principles of justice and social welfare. Islam encourages a fair economic system, where the prices of goods are not only influenced by market forces but also take into account the welfare of the people